2023
DOI: 10.3390/pharmacy11010009
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Systematic Literature Review of the Role of U.S. Pharmacists in Prescribing Pre-Exposure Prophylaxis (PrEP)

Abstract: Pre-Exposure Prophylaxis (PrEP) is an effective treatment to combat the human immunodeficiency virus (HIV) endemic, but the uptake of PrEP has been low in the United States (U.S.). While individuals may access PrEP via obtaining a prescription from their prescriber and having it dispensed by their pharmacist, less cumbersome access points may exist. This systematic literature review evaluates qualitative literature to explore the role of pharmacists, pharmacy services, and interprofessional collaborations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…If there was a lack of facilities, pharmacists reported that allowing clients to self‐test themselves for HIV [ 72 ] or having a collaborative service with other healthcare providers could help facilitate PrEP delivery, adherence and continuation [ 31 , 39 , 58 , 61 , 67 ]. Having a clear referral process for pharmacists to provide clients with the necessary treatment options for conditions identified during PrEP delivery was also found to facilitate PrEP delivery [ 73 ].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…If there was a lack of facilities, pharmacists reported that allowing clients to self‐test themselves for HIV [ 72 ] or having a collaborative service with other healthcare providers could help facilitate PrEP delivery, adherence and continuation [ 31 , 39 , 58 , 61 , 67 ]. Having a clear referral process for pharmacists to provide clients with the necessary treatment options for conditions identified during PrEP delivery was also found to facilitate PrEP delivery [ 73 ].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…If there was a lack of facilities within the pharmacy, pharmacists reported that allowing clients to test themselves for HIV (65) or having a collaborative service with other health care providers could help facilitate PrEP delivery, adherence and continuation (28, 30, 42, 61, 62). Having a clear referral process for pharmacists to provide clients with the necessary treatment options for conditions identified during PrEP delivery was also found to facilitate PrEP delivery (35).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…For example, partnerships with pharmacies have been effective in distributing vaccines for COVID-19, influenza, shingles, and other preventable diseases. Future studies of novel PrEP regimens could collaborate with pharmacies 74,75 during clinical trials to set up best practices in dissemination early on. Upon regulatory approval, these regimens could be rolled out without delay to those without clinical providers, insurance, or other access to PrEP.…”
Section: Costmentioning
confidence: 99%